Translation Excellence : Assessment, Achievement, Maintenance. - Gaddis Rose, Marilyn (John Benjamins Pub. Co., 1987)
This inaugural volume transcends its archival value. Indeed, taken as a whole, the essays pose a provocation for both translation practice and theory. The criteria proposed and the issues examined remain the same. Absolute excellence, however, continues to move beyond the horizon, and changes in technology and taste inevitably change both the implementation of the criteria and the evaluation of the issues. The attendant ambiguities may stem from a parenthesis in the volume: does excellence lie in the "X-factor that elusive quality which renders one translation clearly superior to others"?